Pengetahuan dan Tingkat Kecemasan Ibu dalam Merawat Bayi Berat Lahir Rendah (BBLR) (Pendekatan Cross Sectional) - Maulidia, Rahma; Ajeng, Lumastari (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2025)
Nifas's mother who nursed babies with low birth weight (BBLR) was susceptible to anxiety because babies needed special attention. Anxiety often occurs when a woman transforms to a new role asa mother in caring for her baby. The study aims to analyze the relation of knowledge to the anxiety that Mrs. Nifas has in nursing a low-born weight (BBLR) baby in the labor district of the city center of kediri. A sample of this study is all nifas's mothers who gave birth to BBLR in march-april 2025 as many as 35 people. The data-collecting instrument consists of the nifas mother's knowledge questionnaire in caring for BBLR and gad-7. The data is analyzed with the spearman rank test. There 'sa significant link between knowledge and maternal anxiety in nursing a lower birth weight (BBLR) and -0,000 value. Good knowledge tends to have low anxiety because maternal worry can result from inadequate information about BBLR's treatment. The increased knowledge that nifas's mother is needed in order to care for her baby and to prevent anxiety in nifas' mother.